IMPACT OF SURVEY READINESS TRAINING ON NURSING HOME QUALITY OF CARE. (11th November 2018) - Phillips, L; Oyewusi, C; Martin, N; Youse, L; Rantz, M
Abstract: Due to their role overseeing administrative, operational, and clinical services in nursing homes (NHs), licensed nursing home administrators (LNHAs) are responsible for quality of care and correcting deficiencies identified during the annual certification and survey process. State regulations vary widely in educational and work experience requirements for LNHAs. As an adjunct to traditional education, the Quality Improvement Program for Missouri offers on-site 2-day survey readiness training from experienced LNHA-consultants to better prepare current LNHAs. We compared deficiency data from the nearest survey completed before and after LNHAs participated in survey training. NH data were retrieved from Nursing Home Compare and LNHA turnover data from Missouri Department of Health and Senior Services. Of Missouri's 499 NHs, 47 participated in survey training between 7/1/15–6/30/16. Most NHs were for profit (66%) with an average of 100 beds. LNHA-consultants spent an average of 623 minutes at each NH. LNHA turnover, ≤ 1 year before and after survey training, was 0.42 (0.74) and 0.36 (0.79), respectively. Total health deficiencies declined from 5.5 (4.7) before survey training to 4.7 (3.4) (p>.05) after training, whereas life safety deficiencies increased from 2.5 (2.7) to 3.0 (3.2) (p>.05). Profit status was unrelated to deficiencies. Before survey training, health deficiency scope/severity was higher for G (4.3%) and J (6.4%) than after training (2.1% G; 0% J). Trends toward improvement in health deficiencies suggest benefits from LNHA-consultation. A larger sample with control NH, staffing, LNHA education and experience data is needed to comprehensively evaluate the effect of consultation on survey outcomes.